Identification of Blue Horizontal-branch Stars Using Synthetic SkyMapper Colors from Gaia XP Spectra - Guozhen Hu; Yang Huang; Wenyuan Cui; Tao Wang; Kai Xiao; Ruifeng Shi; Jie Ju; Bowen Huang; Chunyan Li; Zhicun Liu; Xiaolong Wang; Changqing Luo (The Astrophysical Journal Supplement Series)
Blue horizontal-branch (BHB) stars are ideal tracers for mapping the structure of the Galactic stellar halo. Traditionally, BHB sample stars are built from large-scale spectroscopic surveys utilizing their spectral features; however, the resulting sample sizes have been quite limited. In this paper, we construct a catalog of BHB stars based on synthetic colors ( u  −  v ) _0 and ( g  −  i ) _0 in SkyMapper photometric systems, which are convolved from Gaia XP spectra. A total of 49,733 BHB stars are selected from nearly the entire sky (excluding regions of low Galactic latitudes ∣ b ∣ ≤ 8 ^∘ with heavy reddening), with a completeness and purity exceeding 90%. Using member stars of globular clusters with precise distance determinations, we carefully calibrate the relationship between the g -band absolute magnitude and ( g  −  i ) _0 , achieving a precision of 0.11 mag, which corresponds to a 5% uncertainty in distance. This relation is applied to derive distances for all BHB stars in the constructed sample. Given the current capabilities of Gaia XP observations, the constructed BHB sample is primarily located within 20 kpc, enabling detailed mapping of the inner stellar halo. To extend this depth to the outer halo or even the edge of our Galaxy, we explore the potential of the Chinese Space Station Telescope (CSST) and its broadband photometry for detecting BHB stars. Using mock data from synthetic spectra, we find that it is feasible to distinguish BHB stars from blue stragglers stars using CSST near-ultraviolet band ( u ) photometry. Thanks to the deep limiting magnitude of CSST, its data will provide a groundbreaking perspective on our Galaxy, particularly regarding the outer halo, in an unprecedented volume.